Drag teen : a tale of angst and wigs - Self, Jeffery (PUSH, an imprint of Scholastic Inc., 2016)
JT is a gay high school senior determined to get out of Clearwater, Florida, and be the first person in his family to go to college, even though he can not figure out how to pay for it--until his friends convince him to compete in a drag teen competition where the first prize is a college scholarship.